Evaluasi Keutuhan Borepile Metode Crosshole Sonic Logging (CSL) Pembangunan Jembatan Pulau Balang II - Juandra Hartono (Jurnal Aplikasi Teknik Sipil, 2021)
The problem that occurs in the Balang II Island Bridge construction project in East Kalimantan Province is the blockage of concrete flowing through the tremi pipe when casting the borepile foundation at sea. A considerable distance from the initial location of the tremi pipe (on land) to the endpoint of casting requires a fairly long tremi pipe. This blockage causes the concrete to flow imperfectly. There are many speculations about the cause of this problem, including leaks in the tremi pipe and the uniformity of the concrete mix. Based on these problems to prevent the failure of the foundation structure, an integrity test will be carried out on non-destructive piles. The integrity test to be carried out is in the form of a Crosshole Sonic Logging Test (CSL). The results of the CSL test on pylon P1 show that of the 17 borepile piles tested 2 piles have abnormalities, namely the P1-64 pile with the P/D category on the whole cross-section and the P1-52 P/F category on some sections (± 40%). Overall it can be concluded that the integrity of the drill pile on pylon P1 is still quite safe.